THE TRIBOLOGICAL PROPERTIES OF HETEROGENEOUS COATINGS - Кіндрачук, М. В.; Кульгавий, Е. А.; Перро, Д. І.; Подлєсний, В. О. (Science-based technologies, 2009)
Tribological properties of heterogeneous coatings defined by the properties of self-generated in contact dissipativestructures. In the work are present characteristics of wear coatings in analytical form, and also results ofanalysis of tribological structures.